(untitled) (Biological Sciences - PJSIR, 1995)
The use of water-hyacinth root, rice straw and dried grass as mulches was evaluated for their effects on the growth and yield of late planted garlic at Bangladesh Agricultural University farm during 1990-91 growing season. Plants treated with any kind of mulches under study significantly increased plant height. number of leaves per plant. length of leaf, length of pseudostem, number of roots per plant, bulb and neck diameter over the control. These mulches significantly influenced bothon chlorophyll-a andchlorophyll-b contents. Bulb length.bulb diameter, clove length, clove diameter, clove number per bulb. 100 clove weight and yield were also significantly higher in plants treated with mulches. All mulches provided weed control as well. Among the treatments. water-hyacinth root was proved to be superior asmulching materialinproducing garlic.Alltypes ofmulches inthis study highly compensated the reduction of yield of garlic due to late planting.